Peran Pendidikan Al-Qur’an dan Hadis Terhadap Pembentukan Kebudayaan Islam - Maulana Ismail; Miftahul Jannah; Finna Rahmatia; Herlini Puspika Sari (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2025)
This study aims to analyze the influence of Qur'anic and Hadith education on the formation of Islamic culture in the historical trajectory. By using a qualitative approach and literature study, this study traces how the values of revelation were internalized through the educational process since the time of the Prophet Muhammad until the development of Islamic educational institutions such as madrasah and pesantren. The research approach used is qualitative with a library research method. This means that this research relies entirely on existing data and does not involve data collection in the field. The data collection technique is done through documentation, namely identifying, reviewing, and analyzing various relevant literatures. The main data sources include books of Qur'anic commentaries, Hadith commentaries, books on Islamic history, works on Islamic civilization, scientific journals, and research articles related to Islamic education, the Qur'an, Hadith, and Islamic culture. The data analysis technique applied is content analysis with a descriptive-interpretative approach. The collected data are classified, organized, and then interpreted to find patterns, themes, and causal relationships between Qur'anic and Hadith education and the characteristics of Islamic culture. Qur'anic and Hadith education not only creates religious understanding, but also shapes the culture of knowledge, social morality, and artistic expression that is unique to Islamic society. The culture of calligraphy, mosque architecture, and Islamic literature are tangible manifestations of the influence of Islamic education on the lives of the people. The results show that Islamic education plays an important role in building a civilization rooted in spiritual and intellectual values. In the modern era, these values remain relevant as a solution to global challenges, such as identity crisis and moral degradation. Thus, Qur'anic and Hadith education needs to be continuously revitalized so that Islamic culture can develop contextually and sustainably. Kata Kunci: Pendidikan Islam, Al-Qur’an, Hadis, Kebudayaan Islam, Nilai-Nilai.